Body fat percentage assessment by skinfold equation, bioimpedance and densitometry in older adults - Erika Aparecida Silveira; Larissa Silva Barbosa; Ana Paula Santos Rodrigues; Matias Noll; Cesar De Oliveira (BMC, 2020)
Abstract Background Body fat estimation allows measuring changes over time attributed to interventions and treatments in different settings such as hospitals, clinical practice, nursing homes and research. However, only few studies have compared different body fat estimation methods in older adults with inconsistent results. We estimated body fat percentage (%BF) and the level of agreement among dual energy X-ray absorptiometry (DXA), bioelectrical impedance (BIA) and Durnin & Womersley's skinfold eq. (SF) in older Brazilian adults aged 60 years and older from the Elderly Project Goiânia, Brazil. Methods The analytical sample comprised of 132 participants who had DXA data. The level of agreement for the %BF estimated by BIA, SF and DXA i.e. reference method, was examined using Bland and Altman's and Lin's plot. Results Overall, women had higher body mass index and %BF values measured by all three methods used. BIA and SF equation showed strong concordance to estimate body fat percentage in all participants (CCC = 0.857 and 0.861, respectively) and among women (CCC = 0.788 and 0.726, respectively) when compared to DXA. However, both methods underestimated body fat percentage in women and men with high body fat percentage. A strong level of agreement was observed between DXA and the anthropometric equation developed by Durnin & Womersley in men (CCC = 0.846), while BIA had a moderate concordance (CCC = 0.505) in this group. Conclusion The examined methods indicated different body fat estimates. However, the best agreement was observed between DXA and the anthropometric SF equation for men. Future research in older adults should develop new SF equations considering different ethnic groups.